Gas concentration and temperature excited Delft turbulent jet in acoustically flames - Rocha, Ana Maura A. [UNESP]; Carvalho, Joao A.; Lacava, Pedro T. (Elsevier B.V., 2008)
This paper shows the experimental results for changes in the flame structure when acoustic fields are applied in natural gas Delft turbulent diffusion flames. The acoustic field (pulsating combustion) generates zones of intense mixture of reactants in the flame region, promoting a more complete combustion and, consequently, lower pollutant emissions, increase in convective heat transfer rates, and lower fuel consumption. The results show that the presence of the acoustic field changes drastically the flame structure, mainly in the burner natural frequencies. However, for higher acoustic amplitudes, or acoustic pressures, a hydrogen pilot flame is necessary in Older to keep the main flame anchored. In the flame regions where the acoustic field is more intense, premixed flame characteristics were observed. Besides, the pulsating regime modifies the axial and radial combustion structure, which could be verified by the radial distribution of concentrations of O-2, CO, CO2, and NOx, and by the temperature profile. The experiments also presented the reduction of flame length with the increase of acoustic amplitude. (c) 2008 Published by Elsevier Ltd.
Keywords: pulsating combustion; turbulent jet flames; acoustically excited flame; Delft burner